Comparison of Thoracic and Abdominal Cavity Volumes During Abdominal CO2 Insufflation and Abdominal Wall Lift. Issue 5 (15th November 2012) - Watkins, Courtney; Fransson, Boel A.; Ragle, Claude A.; Mattoon, John; Gay, John M.
<x xml:space="preserve">Abstract</x> Objective To compare thoracic and abdominal cavity volumes during abdominal CO2 insufflation and abdominal wall lift (AWL) conditions. Study Design In vitro cadaveric study. Animals Mature medium‐to‐large breed fresh canine cadavers (n = 6). Methods Each cadaver was imaged with computed tomography (CT) under baseline, abdominal CO2 insufflation, and AWL conditions. Measurements of thoracic and abdominal cavities were performed for each condition using image‐analyzing software. Resulting volumes for each cadaver were converted to percent change from baseline to normalize the data. The t‐tests were used to compare percent changes of both thoracic and abdominal volumes. Results Thoracic volume significantly decreased from baseline during CO2 insufflation (P < .01). No significant difference in thoracic volume occurred with AWL when compared with baseline. Abdominal volume increased by 80% with CO2 insufflation (95% CI: 56.4–107.0%) but only 25% with AWL (95% CI: 12.3–37.8%). Conclusions Abdominal CO2 insufflation results in decreased thoracic volume when compared with baseline. AWL preserved thoracic volume similar to baseline. Abdominal volumes achieved with abdominal CO2 insufflation are significantly greater than those attained with AWL.